Spinal Muscular Atrophy - The disease and its treatments - Kyra Y. Chen (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Less than a decade ago, patients diagnosed with Spinal Muscular Atrophy (SMA) had no treatments other than pulmonary, gastrointestinal, and orthopedic care. These palliative treatments were focused on managing symptoms and did not address the cause of the disease itself. Now, there are several FDA (U.S. Food and Drug Administration) approved drugs to treat SMA, which can stop or slow disease progression. In order to discuss the development of treatments for patients with SMA, the disease must first be explained in detail.